On Active Surge Control of Compression Systems via Characteristic Linearization and Model Nonlinearity Cancellation - Yohannes S.M. Simamora; Harijono A. Tjokronegoro; Edi Leksono (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
A simple approach of active surge control of compression systems is presented. Specifically, nonlinear components of the pressure ratio and rotating speed states of the Moore-Greitzer model are transferred into the input vectors. Subsequently, the compressor characteristic is linearized into two modes, which describe the stable region and the unstable region respectively. As a result, the system's state and input matrices both appear linear, to which linear realization and analysis are applicable. A linear quadratic regulator plus integrator is then chosen as closed-loop controller. By simulation it was shown that the modified model and characteristics can describe surge behavior, while the closed-loop controller can stabilize the system in the unstable operating region. The last-mentioned was achieved when massflow was 5.38 per cent less than the surge point.